Spectrophotometric Assay of Allicin in Iranian Garlic Products - Sariri, Reyhaneh; Aliakbar, Alireza; Bashiri Mesdarghi, Ghader; Rezazadeh, Alireza (Asian Journal of Chemistry, 2010)
Allicin (diallyl thiosulfinate) is considered the most important biologically active organosulfur compound found in crushed garlic (Allium sativum Linn.). The amount of allicin in Iranian garlics (grown in North) and some commercially available garlic products has been determined by a UV spectroscopic method. This simple spectrophotometric method has the advantage of not requiring an allicin standard for quantitative determination of allicin. It was found that the amount of total thiosulfinates and allicin is slightly different in various garlic extracts and is significantly higher than its quantity reported by others using garlic from different parts of the world. Variations in the amount of thiosulfinates may be related to climate conditions where garlic is grown.